Dakwah Bilhal Muhammadiyah : Filantropi Dalam Pengentasan Kemiskinan di Surabaya - Mukayat, Al-amin (Universitas Muhammadiyah Surabaya, 2022)
One of the urban problems is poverty, as is the case in Surabaya, which had a poverty rate of 136.37 thousand people in 2023. This poverty rate is the result of the Surabaya city government's intervention through various poverty alleviation programs. Previously, the poverty rate in Surabaya was 138.21 thousand people in March 2022, which decreased to 136.37 thousand people in March 2023. The success of the Surabaya city government in reducing poverty raises the question of whether this reduction in poverty is purely due to government intervention through its programs, or if there is also a role played by social institutions, specifically LAZIS Muhammadiyah Surabaya, which has poverty alleviation programs similar to those implemented by the Surabaya government. This research uses a qualitative research method with an empirical approach. In this study, it was found that LAZISMU (Lembaga Zakat Infak dan Shadaqah Muhammadiyah) Surabaya focuses on helping the poor residents of Surabaya to alleviate their burdens through at least six main programs, namely: education, health, social-humanitarian, economy, environment, and dakwah (Islamic preaching). These programs are almost identical to those carried out by the Surabaya government in its poverty alleviation interventions. Our research found that the social philanthropy programs conducted by LAZISMU Surabaya contributed to the reduction of poverty in Surabaya. Keywords: Poverty, Philanthropy, LAZISMU